(untitled) (INTERNATIONAL SEMINAR, 2025)
Digital payment systems and fintech lending services in Indonesia have made shopping and borrowing easier, but they also bring new legal and security risks. This article examines the effectiveness of consumer protection regulations governing digital payments and fintech lending in Indonesia using a normative legal approach. The research examines whether existing regulations such as the Consumer Protection Law, Bank Indonesia regulations on payment systems, and the Financial Services Authority (OJK) regulations on consumer protection in the financial sector are sufficient to address issues such as transparent fees, fair debt collection practices, misuse of personal data, and online transaction security. By examining relevant laws, policies, and principles, this study identified gaps in current regulations and examined how well consumer rights are protected in practice. The results show that while regulations have improved, their implementation remains inconsistent, particularly regarding unauthorized data use and aggressive data collection practices. The study recommends a more integrated, consumer-rights-based approach, with a focus on harmonizing regulations, improving oversight, and establishing clear accountability standards for fintech providers and digital payment platforms.